Peran Tradisi Ter-ater dalam Teori Fungsionalisme Talcot Persons Terhadap Stabilitas Sosial - Fatimatuz Zahroh; Moh Elman; Moh. Ruddin; Abdul Hakim (IAIN Madura, 2025)
This research examines the role of ter-ater traditions in the social stability of Madurese society, especially in Blumbungan Village, Pamekasa Regency using Talcott Parsons' functionalist theory approach. The issue raised is how the ter-ater tradition contributes to social balance at the village level and its role in strengthening relations between residents. The aim of this research is to analyze the impact of ter- ater traditions on the social structure and stability of village communities. The method used is qualitative research using observation and interview techniques with community leaders, traditional leaders and residents of Blumbungan Village. The results of research on the Ter-Ater tradition have proven effective in maintaining social order in Blumbungan Village. Ter-Ater functions as a medium to strengthen relations between residents, solving social problems. In the perspective of Talcott Parsons' functionalist theory, ter-ater acts as an important element in the social structure of Blumbungan Village which maintains social harmony and balance. Ter-Ater strengthens social ties between citizens and ensures positive interactions that support stability despite the challenges of globalization and modernization.